Cardiovascular alterations in patients with excessive erythrocytosis in residents at 5,200 meters above the sea level - Quispe-Trujillo, Mariela M. (2020)
Objective: to describe cardiovascular function and determine cardiac disturbances in patients with and without excessive erythrocyteosis (EE). Materials and methods: a prospective, transversal and analytical type study. The sample was of 61 resident patients of the Centro Poblado La Rinconada, located in Puno – Peru, located at 5,200 meters above the sea level. A data collection sheet was used, Qinghai's chronic mountain sickness score was applied, and an experienced cardiologist performed echocardiographies. Results: the average age was 44 ± 7 years and the residence time was 16 ± 9.8 years. Of the total number of patients, 80.3% had chronic mountain sickness; of these, 68.9% were mild grade, 6.6% moderate grade and 4.9% severe grade. Among the echocardiographic findings were found: dilation of cardiac cavities (16.4%), slight alteration of the filling of the right ventricle (3.27%), bicuspid aortic valve (3.27%), difficulty filling the left ventricle (8.2%), slight alteration in relaxation and filling of the left ventricle (1.6%), mild aortic insufficiency (1.6%) pulmonary hypertension (1.6%). 83.6% had hemoglobin ≥ 21 mg/dL. Conclusions: the group with EE had more cardiac disturbances, the most common cardiac disturbance was the dilation of right heart chambers.